WOMEN AND CHILD ABUSE IN SOUTH AFRICA: LESSONS FROM PRACTICE - Hanson, Sheri (Social Work/Maatskaplike Werk, 2011)
A South African exploratory research study (Hanson, 2008) focusing on the phenomenon of the co-occurrence of woman and child abuse in the same family system confirmed international findings (Beeman & Edleson, 2000; Park & Kahn, 2000) that this phenomenon, although poorly recognised, does exist. Although international research findings point to an increase in the co-occurrence of woman and child abuse, it remains largely misunderstood in South Africa, with organisations and social workers addressing either woman abuse or child abuse, but not the two together (Hanson, 2008; Hanson & Patel, 2009; Hanson & Patel, 2010). The study revealed that organisational policies and mandates as well as the theoretical frameworks of the social workers shape the way in which the co-occurrence of woman and child abuse is understood and limits intervention directed at both the mother and the child (Hanson, 2008; Hanson & Patel, 2010).